1975
DOI: 10.1185/03007997509114791
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind trial of methocarbamol versus placebo in painful muscle spasm

Abstract: A double-blind trial of methocarbamol versus placebo was carried out in 59 matched pairs of patients suffering from painful muscle spasm. Methocarbamol (1500 mg. q.d.s.) was found to be effective in approximately 60% of patients compared with 30% of patients receiving placebo (p less than 0.01). Side-effects were of almost equal incidence in the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 5 publications
0
10
0
2
Order By: Relevance
“…Internists have used this drug effectively for many years for patients with low back pain [5]. Considered a good treatment for muscle spasm [14], methocarbamol is a centrally acting muscle relaxant with a mildly sedating and anxiolytic effect at the central nervous system level [4]. This agent has a low likelihood for abuse [11], and has been used effectively in combination with narcotics for relief of postoperative chest pain after surgical placement of breast implants [12].…”
Section: Discussionmentioning
confidence: 99%
“…Internists have used this drug effectively for many years for patients with low back pain [5]. Considered a good treatment for muscle spasm [14], methocarbamol is a centrally acting muscle relaxant with a mildly sedating and anxiolytic effect at the central nervous system level [4]. This agent has a low likelihood for abuse [11], and has been used effectively in combination with narcotics for relief of postoperative chest pain after surgical placement of breast implants [12].…”
Section: Discussionmentioning
confidence: 99%
“…Theimprovements were significant for sevent onine days of therapy butdecreased in magnitudeo vert ime.T he authors hypothesized thatthis wasdue to the self-limiting nature of the injuriesstudied. Asimilarstudy (29) found similari mprovements with the incidenceo fs ide effectse qualt ot hato ft he placebo.…”
Section: Vetcomp Orthoptraumatol4/2005mentioning
confidence: 70%
“…Methocarbamol is ac entrallya cting musclerelaxantthatselectivelyblocks polysynapticreflexpathwaysinthe spinalcord without anye ffect on monosynapticp athways.I td oesn ot have anyd irect effect on the contractile elements of skeletal muscle, the somatic nerves, or the motor endp late (29),and itspharmacokinetics in dogs have been established ( 8). One early placebocontrolled study evaluated the efficacyo f methocarbamol in humans with acute musclepaindue to traumatic or inflammatoryi njury ( 28).…”
Section: Vetcomp Orthoptraumatol4/2005mentioning
confidence: 99%
“…Relief of acute painful musculoskeletal conditions Dosage 1500 mg,four times daily Oral Physician's Desk Reference (2003), Valtonen (1975), Tisdale and Ervin (1975) Reduce dose to 750 mg every 4 h or 1500 mg three times daily for maintenance.…”
Section: Reference Commentsmentioning
confidence: 99%